Starling Lawu Dance as a Learning Resource for Movement System for Junior High School Students - Tasya Novian Indah Sari; Suhartini; Suyitno Aloysius (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Movement system material learning requires direct experience to find concepts and associate them with the real world. The need for teaching materials based on local culture in learning biology is one of the important needs to bring students in traditional knowledge and values in the community environment. The purpose of this study was to analyze the motions of starling's lawu dance as a learning resource in the movement system material for grade VIII Junior High School students. This research is a type of exploratory descriptive research. The informant of this study was a science teacher at Junior High School. Data collection techniques were carried out by interviews, FGDs, and assessment of the feasibility of learning resources. Data analysis techniques are used in descriptive research through the stages of data reduction, data presentation, and data conclusion. The results of the study show that there are 22 motion vectors for the starling lawu dance which have the potential to become a source of learning the motion system. The results of the motion analysis of the starling lawu dancers can be used as a basis for further development of teaching materials. Further efforts are needed to package teaching materials based on local culture that is tailored to learning needs.